Intishār al-Lughah al-'Arabīyah wa Mashkulātihi fi Indunīsiyah - Ahmad Abdul Syakur (Al-Jami'ah: Journal of Islamic Studies, 2002)
Arabic (language) is not something new for Indonesian Muslims. Arabic came along with the arrival of Islam in Nusantara. Since then, Indonesian Muslims learn Arabic in various pesantrens, either traditional or modern one. Although Islam has undergone some major developments in its substance and teachings, Arabic has not undergone such major progress. In other words, most pesantrens still employ classical methods in teaching the Arabic. Few pesantrens, however, have developed their methods of Arabic teaching, particularly modern pesantrens such as Pondok Modem Gontor. According to the writer, it is interesting to study these phenomena by viewing some advantages and disadvantages of employing the new methods of Arabic learning. By taking into account of some significant developments in the teaching methods generally, this article is trying to offer an alternative method of Arabic teaching in a way that Indonesian Muslims could learn Arabic easily.